Effects of Welfare Reform on Positive Health and Social Behaviors of Adolescents - Nancy E. Reichman; Hope Corman; Dhaval Dave; Ariel Kalil; Ofira Schwartz-Soicher (MDPI AG, 2023)
This paper explores a missing link in the literature on welfare reform in the U.S.-the effects on positive health and social behaviors of adolescents, who represent the next generation of potential welfare recipients. Previous research on welfare reform and adolescents has focused almost exclusively on negative behaviors and found that welfare reform led to decreases in high school dropout and teenage fertility among girls, but increases in delinquent behaviors and substance use, particularly among boys. Using nationally representative data on American high school students in 1991-2006 and a quasi-experimental research design, we estimated the effects of welfare reform implementation on eating breakfast, regular fruit/vegetable consumption, regular exercise, adequate sleep, time spent on homework, completion of assignments, participation in community activities or volunteering, participation in school athletics, participation in other school activities, and religious service attendance. We found no robust evidence that welfare reform affected any of these adolescent behaviors. In concert with the past research on welfare reform in the U.S. and adolescents, the findings do not support the implicit assumption underlying welfare reform that strong maternal work incentives would increase responsible behavior in the next generation and suggest that welfare reform had overall adverse effects on boys, who have been falling behind girls in terms of high school completion for decades.